2013
DOI: 10.1186/1471-2334-13-65
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the burden of diarrhoeal illness among individuals with and without household cisterns in northeast Brazil

Abstract: BackgroundLack of access to safe and secure water is an international issue recognized by the United Nations. To address this problem, the One Million Cisterns Project was initiated in 2001 in Brazil’s semi-arid region to provide a sustainable source of water to households. The objectives of this study were to determine the 30-day period prevalence of diarrhoea in individuals with and without cisterns and determine symptomology, duration of illness and type of health care sought among those with diarrhoea. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…An example of this can be found in studies related to rural Thailand where the bacterial contamination of shallow well water was higher than that of harvested rainwater (Wirojanagud et al, 1989;Pinfold et al, 1993). This is also the case of the Semi Arid region of Brazil, where the use of rainwater cisterns for drinking purposes has been associated with a decreased occurrence of diarrhea (Marcynuk et al, 2013) and Giardia duodenalis (Fonseca et al, 2014) among rural sparse communities. However, even though in general terms it has been reported that the gastrointestinal diseases in these communities tend to decrease with the use of rainwater, in those cases where rainwater storage lacked from hygiene both coliforms and parasites were detected (Xavier et al, 2011).…”
Section: Bacteria and Pathogensmentioning
confidence: 84%
“…An example of this can be found in studies related to rural Thailand where the bacterial contamination of shallow well water was higher than that of harvested rainwater (Wirojanagud et al, 1989;Pinfold et al, 1993). This is also the case of the Semi Arid region of Brazil, where the use of rainwater cisterns for drinking purposes has been associated with a decreased occurrence of diarrhea (Marcynuk et al, 2013) and Giardia duodenalis (Fonseca et al, 2014) among rural sparse communities. However, even though in general terms it has been reported that the gastrointestinal diseases in these communities tend to decrease with the use of rainwater, in those cases where rainwater storage lacked from hygiene both coliforms and parasites were detected (Xavier et al, 2011).…”
Section: Bacteria and Pathogensmentioning
confidence: 84%
“…In a study of diarrheal illness among individuals with and without RHRW tanks in northeast Brazil, Marcynuk and colleagues 84 assessed the 30-day period prevalence of diarrhea for 3,679 people from 774 households following the institution of the 2011"One Million Cisterns" project that has provided 351,000 RHRW cisterns to families throughout the semi-arid region of northeast Brazil as of 2011. 84 People residing in households with cisterns had a significantly lower 30-day period prevalence (11%) of diarrhea than people from households without a cistern (18%) with the trend remaining in a subgroup analysis of children under five. Children under five had a prevalence of 15.6% compared to 26.7% in children without a cistern.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…From these results, 32 full texts were included, in addition to 56 identified through the snowballing method. The total number of studies included in this review are 88 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ...…”
Section: Resultsmentioning
confidence: 99%